2019
DOI: 10.1021/acssuschemeng.9b00811
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Reduction and Biomass: A Case Study of Sustainable Catalysis

Abstract: Catalysis plays a major role at mitigating the environmental impact of the chemical industry, drastically cutting its energy and material consumption. For this perspective, we have chosen C=O reduction in the context of biomass as a benchmark reaction to introduce and illustrate essential aspects of green catalysis. We first covered the most used C=O hydrogenation substrates made from biomass. Then, we looked at alternative energy sources to convective heating, discussed the use of greener solvents and reducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 241 publications
(419 reference statements)
0
25
0
Order By: Relevance
“…The synthesis of biofuel and high-value fine chemicals from renewable biomass provides a promising approach to sustainable economic development. Lignocellulose, as the most abundant biomass resource, is readily transformed into aromatic platform compounds (such as hemicellulose-derived 5-methylfurfural, cellulose-derived 5-hydroxymethylfurfural, and lignin-derived vanillin). These compounds have a high unsaturated bond and oxygen content, and selective C–O hydrogenolysis of aromatic methyl–OH is an important pathway for upgrading. The hydrogenolysis of 5-methylfurfural (MF) and 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) and vanillin (VA) to 2-methoxy-4-methylphenol (MMP) has received intense attention for the preparation of biobased fuel and fine chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of biofuel and high-value fine chemicals from renewable biomass provides a promising approach to sustainable economic development. Lignocellulose, as the most abundant biomass resource, is readily transformed into aromatic platform compounds (such as hemicellulose-derived 5-methylfurfural, cellulose-derived 5-hydroxymethylfurfural, and lignin-derived vanillin). These compounds have a high unsaturated bond and oxygen content, and selective C–O hydrogenolysis of aromatic methyl–OH is an important pathway for upgrading. The hydrogenolysis of 5-methylfurfural (MF) and 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) and vanillin (VA) to 2-methoxy-4-methylphenol (MMP) has received intense attention for the preparation of biobased fuel and fine chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, much work has been dedicated to the conversion of LvA to GVL, and is reviewed elsewhere. [ 177–183 ] Most promising studies have suggested the use of FA as a reducing agent, as it can decompose into H 2 and CO 2 under appropriate conditions. Indeed, FA is a byproduct of the hydrolysis of biomass into LvA, and its use as a co‐reactant would improve the overall efficiency of the process.…”
Section: Production Of Biobased Acrylates and Analogsmentioning
confidence: 99%
“…21 Pd, Pt, Au, and Ru nanoparticles supported on different carriers are among the most active systems commonly used in the hydrogenation of 5-HMF. 22 Wang et al 12 Co 3 O 4 catalytic system; authors note a 75% yield of BHMF after 10 h of the reaction using 2-propanol as a hydrogen donor at the temperature of 170 °C. A group of researchers led by Fulignati disclosed a maximum yield of BHMF of 79.5% on a Ru/C catalyst at the temperature of 100 °C and H 2 pressure of 3 MPa in 30 min.…”
Section: ■ Introductionmentioning
confidence: 99%